2019
DOI: 10.3174/ajnr.a6176
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal and Retrolaminar Migration of Intraocular Silicone Oil Detected on CT

Abstract: BACKGROUND AND PURPOSE: Intraocular silicone oil injection has been used to treat complicated retinal detachments, and recently its retrolaminar and intracranial migration has been reported. The purpose of this study was to document the prevalence of posterior migration of intraocular silicone oil on head CT and describe the clinical and radiologic findings. MATERIALS AND METHODS: This retrospective study included 57 patients with intraocular silicone oil injection who underwent unenhanced head CT between Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Ultrastructural studies have shown alterations in lens epithelial cells [7][8][9] . Cataracts are also a cause of low vision and its removal should be scheduled at the same time of SO removal, considering the corneal endothelial cell count, which could be altered by the effect of SO [23][24][25][26][27][28][29][30][31][32][33][34] . In our review we found that this is the main complication reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural studies have shown alterations in lens epithelial cells [7][8][9] . Cataracts are also a cause of low vision and its removal should be scheduled at the same time of SO removal, considering the corneal endothelial cell count, which could be altered by the effect of SO [23][24][25][26][27][28][29][30][31][32][33][34] . In our review we found that this is the main complication reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors believe that OHT could be associated, but there are no studies with a robust methodology to confirm any of these theories. Rates range from 3.3% to 5.9% of cases [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios ultraestructurales han demostrado alteraciones en las células epiteliales del cristalino [7][8][9] . La catarata es también causa de baja visión y debe considerarse su extracción cuando se planifique el retiro del AS, teniendo en consideración el recuento de células endoteliales corneales, el cual podría estar alterado por el efecto del AS [23][24][25][26][27][28][29][30][31][32][33][34] . En nuestra revisión encontramos que esta es la principal complicación reportada.…”
Section: Discussionunclassified
“…Muchos autores creen que la HTO podría estar asociada, pero no existen estudios con metodología de peso para afirmar ninguna de estas teorías. Las tasas van del 3.3% al 5.9% de los casos [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Discussionunclassified
“…Silicone oil migration is usually an asymptomatic entity however it has been associated with neurological symptoms such as headache, dizziness and seizures [6]. Silicone oil on CT images presents as a hyperdense lesion with predilection of non-dependent locations secondary to the lower specific gravity in relation to the cerebrospinal fluid [7]. On average specific gravity for silicone oil used in ocular surgery is 0.97 g/cm 3 whereas specific gravity of CSF ranges from 1.0063 to 1.0075 g/cm 3 [8,9].…”
Section: Introductionmentioning
confidence: 99%